Fitness Evaluation of Two Component Release of Insects Carrying Dominant Lethality (RIDL) Based Transgenic Aedes aegypti Mosquito Lines - Dilani, P.V.D.; Dassanayake, R.S.; Dilruk, H.M.; Hapugoda, M.; Zurita, F.; Hettiarachchi, C.; Gunawardene, Y.I.N.S. (University of Colombo, 2024)
Transgenic Aedes aeopti mosquito lines are developed for effective dengue control. A two-component RIDL system, with driver and effector transgenes, was previously engineered into the mosquito genome to create two separate transgenic lines. ...
Keywords: Ae Aegypti; Mosquito; Driver; Effector